Sensory effect of acetaldehyde on the perception of 3‐mercaptohexan‐1‐ol and 3‐isobutyl‐2‐methoxypyrazine. (28th January 2016) - Coetzee, C.; Brand, J.; Jacobson, D.; Du Toit, W.J.
Abstract: Background and Aims: Wine aroma is influenced by complex interactions between various wine constituents. This study investigated the sensory interactive effects of Sauvignon Blanc impact compounds, 3‐mercaptohexan‐1‐ol and 3‐isobutyl‐2‐methoxypyrazine, with acetaldehyde that typically forms during the oxidation of wine. Methods and Results: Spiked model wines were subjected to sensory descriptive analysis using a trained sensory panel. The concentration of each compound varied from below aroma threshold values to high values as reported for wine. Depending on the concentration, acetaldehyde enhanced fruity attributes at a lower concentration, whereas suppression occurred at a higher concentration. Acetaldehyde effectively suppressed the green pepper aroma attribute at certain concentration values, whereas 3‐mercaptohexan‐1‐ol suppressed oxidised green apple associated with acetaldehyde. Changes in attributes used for aroma description also occurred because of change in concentration. Conclusions: Complex sensory interactions may occur between Sauvignon Blanc impact compounds and one of the main oxidation‐derived compounds, acetaldehyde. Acetaldehyde can enhance or suppress pleasant fruity characters depending on the concentration. Significance of the Study: This study showed the potential positive effect of acetaldehyde on white wine aroma when present at a low concentration. Formation of this compound during winemaking and ageing should, however, be controlled because of negative sensory interactions occurring at a higher concentration. This study may also contribute to the sensory characterisation of Sauvignon Blanc wine undergoing oxidation.